Transient Neonatal Diabetes Associated with Imprinting Disorders in 6Q24 Chromosome Part 1. Іmprinted Cluster PLAGL1/HYMAI - A.Ye. Abaturov; Ye.A. Agafonova; V.L. Babich (Zaslavsky O.Yu., 2015)
The article presents modern data on the mechanisms of genetic disorders that lead to the development of neonatal diabetes mellitus associated with the violation of imprinting of 6q24 chromosome. This article contains information about the structure of the imprinted cluster PLAGL1/HYMAI, gene and protein PLAGL1 ZAC1, non-coding RNAs and HYMAI ZAC-AS, the differentially methylated area PLAGL1/HYMAI cluster. It is shown that the cluster ICR PLAGL1/HYMAI hypermethylation is accompanied with PLAGL1 gene transcriptional silencing in cells of various human malignancies, including ovarian cancer, colorectal cancer, sarcoma, glioblastoma and rhabdomyosarcoma, and hypomethylation is associated with transient neonatal diabetes mellitus.